2018
DOI: 10.21037/jgo.2018.08.17
|View full text |Cite
|
Sign up to set email alerts
|

A phase I trial of Proton stereotactic body radiation therapy for liver metastases

Abstract: Background: A phase I trial to determine the maximum tolerated dose (MTD) of Proton stereotactic body radiation therapy (SBRT) for liver metastases in anticipation of a subsequent phase II study. Methods: An institutional IRB approved phase I clinical trial was conducted. Eligible patients had 1-3 liver metastases measuring less than 5 cm, and no metastases location within 2 cm of the GI tract. Dose escalation was conducted with three dose cohorts. The low, intermediate, and high dose cohorts were planned to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…To date, SBPT has primarily been studied in the setting of hepatic metastases and seems to be a safe treatment technique. 25,26 The use of SBPT for HCC is intriguing, as proton therapy was an independent predictor of better OS in an National Cancer Database (NCDB) analysis comparing proton therapy to photon SBRT. 27 The current study is limited by its retrospective nature.…”
Section: Discussionmentioning
confidence: 99%
“…To date, SBPT has primarily been studied in the setting of hepatic metastases and seems to be a safe treatment technique. 25,26 The use of SBPT for HCC is intriguing, as proton therapy was an independent predictor of better OS in an National Cancer Database (NCDB) analysis comparing proton therapy to photon SBRT. 27 The current study is limited by its retrospective nature.…”
Section: Discussionmentioning
confidence: 99%
“…The Karolinksa Institute was the first to report the efficacy and safety of high dose focal liver irradiation using a stereotactic technique in the 1990’s [ 41 ]. Additional centers have prospectively reported on the efficacy and safety of liver SABR, Table 1 [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Our prior review provides more depth on the background and history of the liver SABR [ 3 ].…”
Section: The Evolution Of External Beam Radiation Therapy For Livementioning
confidence: 99%
“…This survival benefit was attributed to a significantly lower mean liver dose, which decreased the risk of non-classic RILD in proton patients [ 73 ]. Additional prospective clinical trials have demonstrated the efficacy and safety of proton liver SABR [ 51 , 53 ]. Just as with photon based therapy, considerations need to be taken for motion management and image guidance with proton radiotherapy.…”
Section: Strategies To Overcome Limitations To Sabrmentioning
confidence: 99%
“…However, the authors note that this is likely related to a lower BED. A phase I dose escalation trial showed Proton SBRT to be safe and well tolerated with the maximal tolerated dose not reached at a dose of 60 GyE (Gray equivalent) (28).…”
Section: Original Articlementioning
confidence: 99%
“…The dose in proton therapy is defined in terms of effective dose, which is the physical dose in Gray multiplied by a relative biological effectiveness (RBE) of 1.1, which has been validated in the clinic (29). The 60 GyE regimen had no dose limiting toxicity and is used for the phase II trial with dose constraints specified by protocol (28). Other patients who did not meet eligibility criteria for the phase II trial were treated in 3 or 5 fractions.…”
Section: Fractionation Schemes and Dose Constraintsmentioning
confidence: 99%